ON LOCATION OF SPIRAL SINGULARITIES OF POWER SERIES. II - Gharibian, T. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this paper problems on location of singularities of power series are investigated which lie outside of its circle of convergence and on prescribed spiral angle. Finite as well as infinite singularities are considered.